2008
DOI: 10.1016/j.neulet.2008.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependence of the 5-HT agonist quipazine in facilitating spinal stepping in the rat with epidural stimulation

Abstract: Epidural electrical stimulation (ES) at spinal cord segment L2 can produce coordinated step-like movements in completely spinalized adult rats [R.M. Ichiyama, Y.P. Gerasimenko, H. Zhong, R.R. Roy, V.R. Edgerton, Hindlimb stepping movements in complete spinal rats induced by epidural spinal cord stimulation, Neurosci. Lett. 383 (2005) [339][340][341][342][343][344]. Plantar placement of the paws, however, was rarely observed. Here, we sought to determine the dose dependence of a 5-HT agonist (quipazine) on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 22 publications
(31 reference statements)
3
59
1
Order By: Relevance
“…We also showed that ES in combination with the administration (intraperitoneal) of the 5-HT agonist quipazine produces a greater number of coordinated plantar steps on a moving treadmill when compared with ES alone or quipazine alone (Gerasimenko et al, 2007;Ichiyama et al, 2008). In those studies, ES plus quipazine acutely changed the physiological state of the lumbosacral spinal cord in a manner that enabled coordinated locomotion to occur in response to proprioceptive input without input from the brain.…”
Section: Introductionmentioning
confidence: 71%
“…We also showed that ES in combination with the administration (intraperitoneal) of the 5-HT agonist quipazine produces a greater number of coordinated plantar steps on a moving treadmill when compared with ES alone or quipazine alone (Gerasimenko et al, 2007;Ichiyama et al, 2008). In those studies, ES plus quipazine acutely changed the physiological state of the lumbosacral spinal cord in a manner that enabled coordinated locomotion to occur in response to proprioceptive input without input from the brain.…”
Section: Introductionmentioning
confidence: 71%
“…Although these levels are not noticeable in the air-stepping paradigm, significant differences do emerge in a testing environment that introduces cutaneous sensory stimulation. Interestingly, Ichiyama and colleagues [33] found quipazine dose-dependent changes in coordination in adult spinal rats. Higher doses of quipazine resulted in a decrease in coordinated movement, as well as the number of plantar steps.…”
Section: Discussionmentioning
confidence: 99%
“…The following challenges were used: (1) MK-801, a glutamatergic NMDA receptor antagonist, at doses of 0.1, 0.2 or 0.3 mg/kg (Bubenikova-Valesova et al 2007; Jacobs et al 2000; Su et al 2007); (2) SKF-82958, a DA D 1 receptor agonist, at doses of 0.1, 1.0 or 2.0 mg/kg (Maneuf et al 1997); (3) quinpirole, a DA D 2/3 receptor agonist, at doses of 0.5, 1.0 or 1.5 mg/kg (Stuchlik et al 2007); or (4) quipazine, a non-selective serotonin 5-HT 2/3 receptor agonist, was given of 0.1, 0.3 or 0.5 mg/kg (Antri et al 2005; Ichiyama et al 2008). All drugs were obtained from Sigma-Aldrich (USA).…”
Section: Methodsmentioning
confidence: 99%